MEDICINAL BIOMAGNETISM FOR ANALGESIA - APPLICATION OF STATIC MAGNETIC FIELDS THROUGH THE LYMPHATIC PROTOCOL FOR PERIPHERAL EDEMA - Smith de Vasconcellos, Andrea; Cristina Fassina, Cassia; Marques Neta, Izidória; Mara Rambo Martini, Angela; Viapiana Bossa, Adriane (Health and Society, 2023)
Dysfunctions in the lymphatic system can cause primary or secondary lymphedema, derived from chronic edema, when the lymphatic system is unable to adequately drain lymph from the tissues, resulting in swelling and pain. Through a cross-sectional experimental clinical study, we sought to evaluate the effect of the Adapted Lymphatic Protocol of Medicinal Biomagnetism on pain in the lower limbs of patients with peripheral edema of lymphatic origin. Medicinal Biomagnetism is a therapeutic system developed in 1988 by Dr. Isaac Goiz Durán that uses static magnetic fields generated by medium intensity magnets. These magnets are applied in pairs, one with a north pole, with a calming effect, and the other with a south pole, which activates areas with organic deficiencies, known as Biomagnetic Pairs. Carried out on four female participants, the study applied the protocol in three sessions, spaced weekly. The results demonstrated a reduction in the measurements of the lower limbs, relief in the intensity of pain and discomfort in the legs, although the lymphedema did not disappear completely. It was concluded that Medicinal Biomagnetism proved to be a non-invasive, accessible approach with few side effects, with the potential to alleviate pain and improve quality of life in patients with peripheral edema of lymphatic origin.